2009
DOI: 10.1603/029.102.0320
|View full text |Cite
|
Sign up to set email alerts
|

Cultivar Preferences of Ovipositing Wheat Stem Sawflies as Influenced by the Amount of Volatile Attractant

Abstract: The wheat stem sawfly, Cephus cinctus Norton, causes severe losses in wheat grown in the northern Great Plains. Much of the affected area is planted in monoculture with wheat, Triticum aestivum L., grown in large fields alternating yearly between crop and no-till fallow. The crop and fallow fields are adjacent. This cropping landscape creates pronounced edge effects of sawfly infestations and may be amenable to trap cropping using existing agricultural practices. The behavioral preference for two wheat varieti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
82
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 67 publications
(91 citation statements)
references
References 26 publications
9
82
0
Order By: Relevance
“…While β-ocimene dominated the volatile blend (about 62 %) of S. nigra, this compound was present in only 6 % of the S. viminalis blend. By studying behavioral orientation, Weaver et al (2009) suggest that (Z) and (E)-β-ocimene determine the suitability for oviposition of the However, the most abundant compound may not be necessary as an orientation cue: a particular ratio of compounds might be essential as previously mentioned (Bruce et al 2005). Other volatile compounds found in our study have been identified as electroantennogramactive in sawflies.…”
Section: Discussionsupporting
confidence: 50%
“…While β-ocimene dominated the volatile blend (about 62 %) of S. nigra, this compound was present in only 6 % of the S. viminalis blend. By studying behavioral orientation, Weaver et al (2009) suggest that (Z) and (E)-β-ocimene determine the suitability for oviposition of the However, the most abundant compound may not be necessary as an orientation cue: a particular ratio of compounds might be essential as previously mentioned (Bruce et al 2005). Other volatile compounds found in our study have been identified as electroantennogramactive in sawflies.…”
Section: Discussionsupporting
confidence: 50%
“…Variation in emissions of volatile chemicals among plant genotypes has been primarily demonstrated in cultivated agricultural plants, such as maize [48], cotton [49], wheat [50], and rice [51], and few studies have reported intraspecific variation in chemical emission in natural populations of plants [52][54]. Chemical profile comparisons in this study between half-and full-sibling avocado trees are correlated with the genetic differences.…”
Section: Discussionmentioning
confidence: 78%
“…Piesik et al (2008) showed that wheat stems reliably produce several volatile compounds that infl uence attraction of female WSS for oviposition. Reeder and Conan diff er for the production of these compounds (Weaver et al (2009). Markers identifi ed in this study will allow derivation of near-isogenic lines to determine the genetic relationship between volatile production and the newly identifi ed QTL.…”
Section: Discussionmentioning
confidence: 93%